PKM Superior Village Chicken Breeding Business Using the Crossbreeding Method in Lepo-Lepo Village, Baruga District, Kendari City - Rusli Badaruddin; Natsir Sandiah; Takdir Saili; Fuji Astuti Auza; Deki Zulkarnain; La Ode Muh. Munadi (PT FORMOSA CENDEKIA GLOBAL, 2023)
UHO Internal Community Partnership Program (PKMI-UHO) activities carried out by the Faculty of Animal Husbandry Lecturer Team are located in Lepo-Lepo Village, Baruga District, Kendari City. Introducing superior free-range chicken breeding techniques through the cross-breeding method to local chicken breeders in Lepo-Lepo Village, Baruga District. This is intended so that breeders can run their livestock businesses in a more focused and coordinated manner. Introducing how to make free-range chicken feed from existing feed ingredients and introducing artificial insemination techniques for free-range chickens which include techniques for storing chicken semen and deposition of semen into the reproductive tract of female chickens. Introducing how to operate a hatching machine properly and correctly. Introducing farmers to vaccinations to prevent disease and treatment of free-range chickens so that livestock productivity is more optimal.